The Effect of Leadership, Motivation and Job Satisfaction on Employee Performance and Compensation as Moderation Variables - Ofar, Moh; Mursidi, Mursidi; Rumijati, Aniek (Business Innovation Management and Entrepreneurship Journal, 2022)
This study aims to examine the influence of leadership, motivation and job satisfaction on employee performance and compensation as a moderation variable of the study on CV. Citiplan in Malang.  The sampling technique uses a saturated sampling technique, with all employee of CV. Citiplan  which is 47 respondents. The analytical tool used is a moderated regression analysis using SPSS. The instrument in this study is the validity test of the reliability test, the test of classical assumptions.  Hypothesis using the T  test  and uji F using SPSS.   The results showed that leadership has a significant influence on employee performance, motivation has a significant influence on employee performance, job satisfaction has a significant influence on employee performance.   Leadership, motivation, job satisfaction has a positive and significant influence on employee performance.  Compensation moderates on the influence of leadership, motivation, work integrity on employee performance.